From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé